Accumulation Characteristics Of Centella Asiatica L. As A Potential Cd-hyperaccumulator In Soil - Sarji, Noor Liyana (2016)
Researchers are becoming fascinated in using hyperaccumulators for sanitization of heavy metal polluted soils. In this study, Centella asiatica L. has been proposed as a potential cadmium (Cd) hyperaccumulator. A series of pot experiments were conducted in this study. Three groups of treatments were emerged which are soil spiked with 10 mgkg'1 of cadmium as cadmium chloride hemi pentahydrate (CdCl2.2.5Il20), 25 mgkg 1 Cd and 40 mgkg'1 Cd into total 15 plastic pots (diameter = 20 cm, height = 13 cm, 2 kg air-dried soil per pot), added with chelating agent which was ethylene diamine triacetic acid (EDTA) and showed the favorable growth of the plants. The concentrations of heavy metals in digested solutions were determined using an atomic absorption spectrophotometer (AAS) using the wavelength of 228.8 nm.